2016
DOI: 10.11144/javerianacali.ppsi14-2.bpfe
|View full text |Cite
|
Sign up to set email alerts
|

Bienestar psicológico en función de la etapa de vida, el sexo y su interacción

Abstract: ResumenObjetivo. Evaluar las diferencias en las dimensiones del bienestar psicológico en función de los grupos de edad, sexo y su interacción. Método. Se obtuvo una muestra de 706 participantes, dividida en tres grupos de edad (jóvenes, adultos y adultos mayores), quienes respondieron a las escalas de bienestar psicológico de Ryff. Se calculó un Manova teniendo en cuenta las variables grupo de edad, sexo y su interacción. Posteriormente, se realizaron varios Anova para conocer entre cuáles grupos existían dife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
36

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 9 publications
3
14
0
36
Order By: Relevance
“…Similarly, the findings in this study are also aligned with studies that identify positive relations with others as one of the main strengths of young people's psychological wellbeing (Mayordomo et al, 2016;Meléndez et al, 2018). They also emphasize the potential of physical-sports activities as a strategy to promote the early development of other dimensions such as autonomy and self-acceptance, which are directly linked to having a more mature personality (Allport, 1961), which has been documented as improving with age (Ryff, 1989(Ryff, , 1991Ryff and Keyes, 1995).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, the findings in this study are also aligned with studies that identify positive relations with others as one of the main strengths of young people's psychological wellbeing (Mayordomo et al, 2016;Meléndez et al, 2018). They also emphasize the potential of physical-sports activities as a strategy to promote the early development of other dimensions such as autonomy and self-acceptance, which are directly linked to having a more mature personality (Allport, 1961), which has been documented as improving with age (Ryff, 1989(Ryff, , 1991Ryff and Keyes, 1995).…”
Section: Discussionsupporting
confidence: 85%
“…Taking as a reference the theoretical model on the construct of wellbeing proposed by Ryff (1989Ryff ( , 1991 based on six theoretical dimensions (self-acceptance; positive relations with others; autonomy; environmental mastery; personal growth, and purpose in life), it has been observed that young people tend to excel in two dimensions, positive relations with others and personal growth (Mayordomo et al, 2016;Meléndez et al, 2018). In contrast, they tend to score lower than other age groups in self-acceptance, autonomy, and environmental mastery (Meléndez et al, 2018), variables that are more characteristic of maturity (Allport, 1961), which tends to evolve positively with age (Ryff, 1989(Ryff, , 1991Ryff and Keyes, 1995).…”
Section: Physical Sports Activities and Psychological Wellbeing In Yomentioning
confidence: 99%
“…Por otro lado, se ha evidenciado en diversos estudios que existe una relación positiva entre el bienestar psicológico y el rendimiento académico (Chow, 2010;Portolés y González, 2015;Salanova et al, 2005;Velásquez et al, 2008). Concerniente a predictores del bienestar psicológico, son varios los autores que afirman que existen diferencias significativas en el bienestar psicológico de acuerdo al género (Burns y Machin, 2010;Del Valle et al, 2015;García-Alandete, 2013;Matalinares et al, 2016;Mayordomo et al, 2016;Muratori et al, 2015;Pineda et al, 2017;Rosa-Rodríguez et al, 2015;Ryff y Singer, 2013;Urquijo et al, 2015;Veliz-Burgos y Urquijo, 2012). Sin embargo Guillén y Angulo (2016) manifiestan que no existen tales diferencias.…”
Section: Introductionunclassified
“…Existen una gran variedad de instrumentos para medir el bienestar psicológico como la Escala de Bienestar Psicológico (BIEPS) de Casullo y Castro (2000), la Escala de Bienestar Psicológico para Adultos (BIEPS-A) de Domínguez (2014), The Questionnaire for Eudaimonic Well-Being de Waterman et al (2010); además McDowell (2010) en su revisión reporta nueve escalas: Life Satisfaction Index, Affect Balance Scale, Singleitem health indicators, The Philadelphia Geriatric Center Morale Scale, General Well-Being Schedule, Satisfaction With Life Scale, Possitive and Negative Affect Scales, The WHO-5 Well Being Index y The Ryff's Scales of Psychological Well-Being. De todos los instrumentos mencionados anteriormente la Escala de Bienestar Psicológico de Ryff es una de las más utilizadas, ésta consta de 39 ítems divididos en seis factores autoaceptación, relaciones positivas con los demás, autonomía, dominio del medio ambiente y propósito en la vida (Aranguren y Irrazabal, 2015;Díaz et al, 2006;Guillén y Angulo, 2016;Mayordomo et al, 2016;Véliz, 2012).…”
Section: Introductionunclassified
“…The psychosocial and emotional changes that occur during aging 1 include a decrease in selfesteem 2 and psychological and subjective well-being 3 and an increase in anxiety 4 , which can lead to the development of depression and in the long term may influence decline in functional and cognitive capacity and subsequent impairment in the quality of life of this population 5 .…”
Section: Introductionmentioning
confidence: 99%